Effectiveness of interventions to indirectly support food and drink intake in people with dementia: Eating and Drinking Well IN dementiA (EDWINA) systematic review. Issue 1 (December 2016) - Bunn, Diane; Abdelhamid, Asmaa; Copley, Maddie; Cowap, Vicky; Dickinson, Angela; Howe, Amanda; Killett, Anne; Poland, Fiona; Potter, John; Richardson, Kate; Smithard, David; Fox, Chris; et al.
Abstract Background Risks and prevalence of malnutrition and dehydration are high in older people but even higher in older people with dementia. In the EDWINA (Eating and Drinking Well IN dementiA) systematic review we aimed to assess effectiveness of interventions aiming to improve, maintain or facilitate food/drink intake indirectly, through food service or dining environment modification, education, exercise or behavioural interventions in people with cognitive impairment or dementia (across all settings, levels of care and support, types and degrees of dementia). Methods We comprehensively searched Medline and twelve further databases, plus bibliographies, for intervention studies with ≥3 cognitively impaired adult participants (any type/stage). The review was conducted with service user input in accordance with Cochrane Collaboration's guidelines. We duplicated assessment of inclusion, data extraction, and validity assessment, tabulating data. Meta-analysis (statistical pooling) was not appropriate so data were tabulated and synthesised narratively. Results We included 56 interventions (reported in 51 studies). Studies were small and there were no clearly effective, or clearly ineffective, interventions. Promising interventions included: eating meals with care-givers, family style meals, soothing mealtime music, constantly accessible snacks and longer mealtimes, education and support for formal and informal care-givers, spaced retrieval and Montessori activities, facilitated breakfast clubs, multisensory exercise and multicomponent interventions. Conclusions We found no definitive evidence on effectiveness, or lack of effectiveness, of specific interventions but studies were small and short term. A variety of promising indirect interventions need to be tested in large, high-quality RCTs, and may be approaches that people with dementia and their formal or informal care-givers would wish to try. Trial registration The systematic review protocol was registered (CRD42014007611) and is published, with the full MEDLINE search strategy, on Prospero (http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42014007611).